RITUAL MA’DULANGKajian Teologis Ritual Ma’dulang dalam InteraksiRambu Tuka’ dan Rambu Solo’ Di Mamullu, Kec. Pana’ Kab. Mamasa - Sarce Sidu; Natalia Sarapang, Thabita Tibuka, Sri Lestari Rahayu, Bartho (CV. ADIBA AISHA AMIRA, 2023)
Indonesia is a country rich in culture. One of them is the Ma'Dulang ritual. The reason for this research is because the authors are interested in examining more deeply the meaning of the ma'dulang ritual theologically, because in it there is a tendency for the community to judge that this ritual should be carried out by people who have ancestral beliefs (aluk todolo) but what happens in society, especially in villages Mamullu, it has been done by people of other religions such as Christians. The ma'dulang ritual is understood as a form of respect as well as hope for deceased ancestors with the hope that every activity carried out in connection with the tu'ka' signs can run well without any obstacles and is carried out in accordance with the law or rules and procedures of aluk todolo. The purpose of this research is to find out the meaning of the ma'dulang ritual and how the relationship between Rambu Tuka' and Rambu Solo' in society. In this study the authors used qualitative research methods with data collection techniques, through library research, observation and interviews. At the end of this article, the writer concludes that some people interpret the ma'dulang ritual to honor and hope for people who have died, with the hope of getting blessings in the form of smooth tuka signs that will be carried out without any problems. However, as a believer in God, you must believe that only God is the source of blessings